Action inhibition in Tourette syndrome. Issue 12 (3rd July 2014) - Ganos, Christos; Kühn, Simone; Kahl, Ursula; Schunke, Odette; Feldheim, Jan; Gerloff, Christian; Roessner, Veit; Bäumer, Tobias; Thomalla, Götz; Haggard, Patrick; Münchau, Alexander
Abstract Tourette syndrome is a neuropsychiatric disorder characterized by tics. Tic generation is often linked to dysfunction of inhibitory brain networks. Some previous behavioral studies found deficiencies in inhibitory motor control in Tourette syndrome, but others suggested normal or even better‐than‐normal performance. Furthermore, neural correlates of action inhibition in these patients are poorly understood. We performed event‐related functional magnetic resonance imaging during a stop‐signal reaction‐time task in 14 uncomplicated adult Tourette patients and 15 healthy controls. In patients, we correlated activations in stop‐signal reaction‐time task with their individual motor tic frequency. Task performance was similar in both groups. Activation of dorsal premotor cortex was stronger in the StopSuccess than in the Go condition in healthy controls. This pattern was reversed in Tourette patients. A significant positive correlation was present between motor tic frequency and activations in the supplementary motor area during StopSuccess versus Go in patients. Inhibitory brain networks differ between healthy controls and Tourette patients. In the latter the supplementary motor area is probably a key relay of inhibitory processes mediating both suppression of tics and inhibition of voluntary action. © 2014 International Parkinson and Movement Disorder Society